Lectotypification of Loranthus thyrsiflorus (Loranthaceae) and its placement in Struthanthu - Kuijt, Job (Phytotaxa, 2014)
The species Loranthus thyrsiflorus Chamisso & Schlechtendal (1828) was based on an unnumbered specimen collected by Friedrich Sellow from an unknown Brazilian locality. Its protologue, unfortunately, does not adequately distinguish the species from most other, presently known, Brazilian entities in Struthanthus, its current generic position. The original material forming the basis of the species was destroyed in Berlin during World War II. The name Loranthus thyrsiflorus has not been typified